Thoracic Wall Reconstruction after Tumor Resection - Harati, Kamran; Kolbenschlag, Jonas; Behr, Björn; Goertz, Ole; Hirsch, Tobias; Kapalschinski, Nicolai; Ring, Andrej; Lehnhardt, Marcus; Daigeler, Adrien (Frontiers in Oncology, 2015)
Introduction: Surgical treatment of malignant thoracic wall tumors represents a formidable challenge. In particular, locally advanced tumors that have already infiltrated critical anatomic structures are associated with a high surgical morbidity and can result in full thickness defects of the thoracic wall. Plastic surgery can reduce this surgical morbidity by reconstructing the thoracic wall through various tissue transfer techniques. Sufficient soft tissue reconstruction of the thoracic wall improves life quality and mitigates functional impairment after extensive resection. The aim of this article is to illustrate the various plastic surgery treatment options in the multimodal therapy of patients with malignant thoracic wall tumors. Material und methods: This article is based on a review of the current literature and the evaluation of a patient database. Results: Several plastic surgical treatment options can be implemented in the curative and palliative therapy of patients with malignant solid tumors of the chest wall. Large soft tissue defects after tumor resection can be covered by local, pedicled or free flaps. In cases of large full-thickness defects, flaps can be combined with polypropylene mesh to improve chest wall stability and to maintain pulmonary function. The success of modern medicine has resulted in an increasing number of patients with prolonged survival suffering from locally advanced tumors that can be painful, malodorous or prone to bleeding. Resection of these tumors followed by thoracic wall reconstruction with viable tissue can substantially enhance the life quality of these patients. Discussion: In curative treatment regimens, chest wall reconstruction enables complete resection of locally advanced tumors and subsequent adjuvant radiotherapy. In palliative disease treatment, stadium plastic surgical techniques of thoracic wall reconstruction provide palliation of tumor-associated morbidity and can therefore improve patient quality of life.